NILAI MORAL DALAM NASKAH DRAMA SAYANG ADA ORANG LAIN KARYA UTUY TATANG SONTANI (KAJIAN SOSIOLOGI SASTRA) - Devi, Ade Anggraini Kartika; Solihat, Ilmi; Wahid, Farid Ibnu (Jurnal Membaca Bahasa dan Sastra Indonesia, 2020)
This research aims to describe (1) the manifestation of moral values in drama script Sayang Ada Orang Lain by Tatang Utuy Sontani and (2) as an effort to enrich teaching material of literature in high school. The subject of this research is drama script Sayang Ada Orang Lain by Tatang Utuy Sontani. This research is focused on an issue related to the analysis of moral values with the sociology of literature approach. Data were analyzed using contentanalysis techniques, which are techniques applied to documents or manuscripts so that they will produce meaning from the manuscripts or documents. The method of data collection is done by using divining manual techniques, listening, and note-taking techniques. The validity of this study was carried out by using investigative techniques by comparing individual opinions with those considered to have the profciency, expertise and competence in accordance with their fields. The results showed as 1) The manifestation of moral values contained in the drama script Sayang Ada Orang Lain by Tatang Utuy Sontani includes: the manifestation of moral values in human relations with the God, with variants in the form of believing in God, obeying and not believing in the existence of God, form moral values in human relationships with themselves, with variants easily discouraged, wise, patient, thinking clearly, betraying the husband, honest, not firm, not steadfast in facing trials, admitting mistakes, regrets, and firm convictions. Then the last is the manifestation of moral values in human relations with other humans in the social sphere, with variants to involving themselves in other people's problems, the wife respects her husband, gives advice, love of the husband to his wife/wife to her husband, help each other, do not respect others, comparing yourself with others, judging others and inciting others. 2) The results of the research on the drama scriptSayang Ada Orang Lain by TatangUtuy Sontani can be used as alternative literary teaching material in high schools in the form of a module entitled "Modul Pembelajaran Drama".